2021
DOI: 10.1177/17562848211059954
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor inhibitors in inflammatory bowel disease: the story continues

Abstract: In the 1990s, tumour necrosis factor-α inhibitor therapy ushered in the biologic therapy era for inflammatory bowel disease, leading to marked improvements in treatment options and patient outcomes. There are currently four tumour necrosis factor-α inhibitors approved as treatments for ulcerative colitis and/or Crohn’s disease: infliximab, adalimumab, golimumab and certolizumab pegol. Despite the clear benefits of tumour necrosis factor-α inhibitors, a subset of patients with inflammatory bowel disease either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 167 publications
(334 reference statements)
0
16
0
Order By: Relevance
“…As TNF‐α is an important necroptosis inducing cytokine, TNF‐α was elevated in the intestine of Casp8 ECko mice (see Fig 2A ), and as anti‐TNF‐α treatment is used in IBD patients (Peyrin‐Biroulet et al , 2021 ), we questioned whether the observed phenotype in Casp8 ECko could be due to TNF‐α signaling. For this, we treated Casp8 ECko mice with the TNF‐α inhibitor Enbrel ® three times per week (Fig 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…As TNF‐α is an important necroptosis inducing cytokine, TNF‐α was elevated in the intestine of Casp8 ECko mice (see Fig 2A ), and as anti‐TNF‐α treatment is used in IBD patients (Peyrin‐Biroulet et al , 2021 ), we questioned whether the observed phenotype in Casp8 ECko could be due to TNF‐α signaling. For this, we treated Casp8 ECko mice with the TNF‐α inhibitor Enbrel ® three times per week (Fig 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…Antitumor necrosis factor drugs were the first biologic agents approved for the treatment of CD. Infliximab is a monoclonal antibody against TNF, which has completely changed the treatment of CD (2). It is effective in improving clinical symptoms and promoting endoscopic healing, but it also has some side-effects, including allergic reaction, increased risk of infection, tumors (e.g., lymphoma), and autoimmune diseases (e.g., psoriasis and systemic lupus erythematosus).…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that by 2030, approximately 1% of the population in industrialized countries will be affected by IBD, which will significantly affect the patient’s quality of life and increase the burden on healthcare systems [ 1 ]. With the development of monoclonal antibodies against tumor necrosis factor (TNF)-α, the management of moderate-to-severe IBD was revolutionized about two decades ago [ 2 ]. Anti-TNF therapy prolongs steroid-free clinical remission, promotes mucosal healing, facilitates closure of fistulas in CD [ 3 ], prevents complications, and improves the patient’s quality of life [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of monoclonal antibodies against tumor necrosis factor (TNF)-α, the management of moderate-to-severe IBD was revolutionized about two decades ago [ 2 ]. Anti-TNF therapy prolongs steroid-free clinical remission, promotes mucosal healing, facilitates closure of fistulas in CD [ 3 ], prevents complications, and improves the patient’s quality of life [ 2 ]. Despite the development of newer biologics with different modes of action, the two anti-TNF agents infliximab (IFX) and adalimumab (ADL) remain first-line biological therapeutics for CD [ 4 ] and UC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation